1975
DOI: 10.1128/aac.7.5.704
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopy of Candida albicans After In Vitro Treatment with Miconazole

Abstract: A study was made on the in vitro action of the antimycotic miconazole on Candida albicans yeast cells with scanning electron microscopy, and the effects were compared with those seen on the yeast cells by means of transmission electron microscopy. It was found that cells exposed to fungistatic and minimal fungicidal doses of miconazole (10-7 M and 10-6 M) presented rough surfaces and had multiple, desoriented buds and bud scars. Whereas in control cultures the cells were well separated, the treated ones formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
41
0
3

Year Published

1976
1976
1988
1988

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 17 publications
4
41
0
3
Order By: Relevance
“…In conclusion, the present findings and the earlier studies on the action of miconazole on membranes of yeasts (9,10,28,33) and mammalian erythrocytes (Sreedhara Swamy et al, in press) show that the drug interacts with both cellular and subcellular membranes.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…In conclusion, the present findings and the earlier studies on the action of miconazole on membranes of yeasts (9,10,28,33) and mammalian erythrocytes (Sreedhara Swamy et al, in press) show that the drug interacts with both cellular and subcellular membranes.…”
Section: Discussionsupporting
confidence: 59%
“…The drug induces leakage of intracellular materials from cells of Candida albicans (28), and at low concentrations it selectively inhibits the uptake of purines and glutamine into these cells (33). Electron microscopic examination of cells of C. albicans exposed to miconazole revealed that the earliest drug-induced alterations are seen at the plasma membrane (9,10). Further, miconazole has been shown to induce hemolysis of mammalian erythrocytes and binds strongly to erythrocyte membrane lipoproteins (Sreedhara Swamy et al, in press).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At the ultrastructural level, C. albicans cells show changes in a dosedependent manner when grown in the presence of 10`8 to 10-M concentrations of miconazole. These changes range from slight alterations in the cell periphery and increase in the number of peroxisomes and lipid globules, to progressive cytoplasmic deterioration, prominent shape changes, and complete cellular necrosis (11,12; S. De Nollin, Ph.D thesis, University of Brussels, Brussels, Belgium, 1976). Recent investigations with scanning and transmission electron microscopy (12) on C. albicans cultures treated with a fungicidal dose of miconazole (10-4 M) have shown that the sequence of alterations differs totally from that obtained with lower-dose treatments.…”
mentioning
confidence: 99%
“…Miconazole and AmB exert their antifungal effect by alteration of fungal cell membrane permeability (4,8,20 Superoxide anion release assay. Superoxide anion (02-) was measured spectrophotometrically at a wavelength of 550 nm by the superoxide dismutase-inhibitable reduction of ferricytochrome c (24).…”
mentioning
confidence: 99%